The Development of Adobe Flash CC (Creative Cloud) Based Interactive Multimedia Module in History Subjects in Grade XI of Senior High School with ASSURE Model - Yeni Novita Sari; Sri Handayani; Marjono Marjono (JURNAL HISTORICA, 2018)
Modules are teaching materials that have features namely self contained, independent, adaptive, and user friendly. The characteristics are relevant to the 2013 Curriculum, approaching student centered learning. The purpose of this research is developing of Adobe Flash CC (Creative Cloud) interactive multimedia module that is validated expertly and effectively as a basic material of learning history XI high school class. This research was using development method (research & development) with ASSURE model. Data collection research used documentation techniques, observation, questionnaire and test. The subject of research involves 3 teachers of subject history and 102 students XI from 3 public high schools in Jember. The results of the interactive multimedia module study showed that, the expert validation of the field of study earned 84%, validation of the linguist score of 87%, and the validation of the media expert 89,47% learning design. Beside that, user test data 1 is obtained 86,66% and user effectiveness test 2 is obtained 65,89%. And rield test is obtained 71,39%. Thus, interactive multimedia modules have been tested expertly and effectively used as learning resource teaching materials.Keywords: Interactive Multimedia Module, Adobe Flash CC (Creative Cloud), ASSURE model